Health Assessment of a Multi-Stakeholder Creative Economy Cooperative using SAK-EP - Alan Wahyu Hafiludin; Driana Leniwati; Nazaruddin Malik (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: Multi-Stakeholder Cooperatives (KMP) represent an economic model that integrates producers, consumers, workers, and investors in one organization. This structure demands transparent and accountable financial reporting practices. This study evaluates the implementation of Private Entity Financial Accounting Standards (SAK-EP) at Let’s Play Game Studio, Indonesia’s first officially registered KMP in the digital game development sector. Methodology/approach: Using a descriptive qualitative method supported by a case study approach, this research conducts an in-depth analysis of the cooperative’s 2024 financial reports to evaluate compliance with applicable accounting standards. Results/findings: The results indicate significant compliance with SAK-EP, particularly in financial statement presentation and revenue recognition, although improvements are needed in disclosure notes and digital transaction documentation. The cooperative’s health assessment places it in the “qualified” category, reflecting sound governance and financial structure. Conclusion: Let’s Play Game Studio demonstrates strong compliance with SAK-EP in financial statement presentation and revenue recognition. However, improvements are needed in disclosure notes and digital transaction documentation to enhance transparency. Its classification as “qualified” reflects stable financial and governance structures. Limitations: The study is limited to a single case (Let’s Play Game Studio) and focuses only on financial reports for the year 2024, which may not fully capture long-term financial health trends or generalize across other KMPs. Contribution: These findings contribute to strengthening accounting practices in creative sector cooperatives and serve as a reference for policy development and cooperative support initiatives.